EVALUASI KEBIJAKAN PENGAWASAN DAN PENGENDALIAN MINUMAN BERALKOHOL DI KABUPATEN SIKKA PROVINSI NUSA TENGGARA TIMUR - Charolus Luanga Saka (Jurnal Ilmiah Wahana Bhakti Praja, 2020)
ABSTRACT. This research focuses on evaluating the supervision and control of alcoholic drinks in Sikka Regency, as an effort to overcome the phenomenon of cultural poverty due to the bias of the community's understanding of the use of moke. The purpose of this study is to evaluate the policy of Supervision and Control of Alcoholic Beverages; know the constraints of the aspects of the substance and the policy environment; and the strategy for Supervision and Control of Alcoholic Beverages. The theory used is the evaluation theory proposed by William N. Dunn. The research design used is a qualitative research with a descriptive approach. The results showed that the supervision and control of alcoholic drinks in Sikka Regency had not been running optimally. In the effectiveness dimension, it was found that the policy formulation process did not go through academic studies, the increase in the number of policies in 2016 was triggered by alcoholic drinks and alcohol intoxication in 2015. On the efficiency dimension, the budget allocation program for increasing safety and environmental comfort from 2014-2016 has increased significantly with the realization of an average of 90% but there are still various cases of violations of K3. The adequacy dimension can be seen from the ratio of the number of civil service police officers to the population of 2017, which is 3: 10,000, the number of PPNS is only one (1) person and the socialization is not optimal. The dimension of accuracy found the fact that the Regent's Decree was not issued on the Integrated Team, the substance of the policy did not explain the definition and standardization of moke. The recommendations of this study: the need for a Regional Regulation on Supervision and Control of traditional alcoholic drinks is preceded by academic studies, public hearings, collaborative outreach, and optimization of the function Linmas in the village. Keywords; Effectiveness; Efficiency; Adequacy; Accuracy.